2023
DOI: 10.1002/ccr3.7458
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic diagnosis of ultra‐early autoimmune gastritis: A case report

Abstract: We describe an ultra-early stage of autoimmune gastritis (AIG) that occurs prior to the well-known early-stage AIG. The key pathology is the shortening of the second layer with degenerated parietal cells. In the management of patients with autoimmune diseases, AIG should be considered even if the endoscopy findings are normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…There was a lack of significant lymphocytic infiltration in Case 2, which diverged from previous reports on early-stage AIG. Terao et al (27) suggested that the identification of early-stage AIG should focus on the slight degeneration of the parietal cells and pseudopyloric gland metaplasia of the chief cells. Our histopathology revealed pseudohypertrophy of the parietal cells and pseudo-pyloric gland metaplasia, supporting the findings of Terao et al Therefore, whether both lymphocytic infiltration and parietal cell degeneration are necessary, and the sequence of their appearance needs to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a lack of significant lymphocytic infiltration in Case 2, which diverged from previous reports on early-stage AIG. Terao et al (27) suggested that the identification of early-stage AIG should focus on the slight degeneration of the parietal cells and pseudopyloric gland metaplasia of the chief cells. Our histopathology revealed pseudohypertrophy of the parietal cells and pseudo-pyloric gland metaplasia, supporting the findings of Terao et al Therefore, whether both lymphocytic infiltration and parietal cell degeneration are necessary, and the sequence of their appearance needs to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Terao et al. ( 27 ) suggested that the identification of early-stage AIG should focus on the slight degeneration of the parietal cells and pseudopyloric gland metaplasia of the chief cells. Our histopathology revealed pseudohypertrophy of the parietal cells and pseudo-pyloric gland metaplasia, supporting the findings of Terao et al.…”
Section: Discussionmentioning
confidence: 99%